An analysis of the social, cultural, and ecological factors that affect the implementation of biosecurity measures on smallholder commercial swine farms in Italy in the context of an emerging African Swine Fever outbreak - Sarah H. Whitaker; Alessandro Mannelli; Uriel Kitron; Silvia Bellini (Preventive Veterinary Medicine, 2024)

Why Do Tamarins Swallow Such Large Seeds? A Response to Heymann’s Commentary - Paul A. Garber; Uriel Kitron (International Journal of Primatology, 2013)

Nonlinear impacts of climatic variability on the density‐dependent regulation of an insect vector of disease - Luis F. Chaves; Amy C. Morrison; Uriel D. Kitron; Thomas W. Scott (Global Change Biology, 2012)
Aedes aegypti is one of the most common urban tropical mosquito species and an important vector of dengue, chikungunya, and yellow fever viruses. It is also an organism with a complex life history where larval stages are aquatic and adults are terrestrial. This ontogenetic niche shift could shape the density‐dependent regulation of this and other mosquito species, because events that occur during the larval stages impact adult densities. Herein, we present results from simple density‐dependent mathematical models fitted using maximum likelihood methods to weekly time series data from P uerto R ico and T hailand. Density‐dependent regulation was strong in both populations. Analysis of climatic forcing indicated that populations were more sensitive to climatic variables with low kurtosis, i.e., climatic factors highly variable around the median, rainfall in Puerto Rico, and temperature in Thailand. Changes in environmental variability appear to drive sharp changes in the abundance of mosquitoes. The identification of density‐independent (i.e., exogenous) variables forcing sharp changes in disease vector populations using the exogenous factors statistical properties, such as kurtosis, could be useful to assess the impacts of changing climate patterns on the transmission of vector‐borne diseases.

Field and climate‐based model for predicting the density of host‐seeking nymphal Ixodes scapularis , an important vector of tick‐borne disease agents in the eastern United States - Maria A. Diuk‐Wasser; Gwenaël Vourc'h; Paul Cislo; Anne Gatewood Hoen; Forrest Melton; Sarah A. Hamer; Michelle Rowland; Roberto Cortinas; Graham J. Hickling; Jean I. Tsao; Alan G. Barbour; Uriel Kitron; et al. (Global Ecology and Biogeography, 2010)
Aim Ixodes scapularis is the most important vector of human tick‐borne pathogens in the United States, which include the agents of Lyme disease, human babesiosis and human anaplasmosis, among others. The density of host‐seeking I. scapularis nymphs is an important component of human risk for acquiring Borrelia burgdorferi , the aetiological agent of Lyme disease. In this study we used climate and field sampling data to generate a predictive map of the density of host‐seeking I. scapularis nymphs that can be used by the public, physicians and public health agencies to assist with the diagnosis and reporting of disease, and to better target disease prevention and control efforts. Location Eastern United States of America. Methods We sampled host‐seeking I. scapularis nymphs in 304 locations uniformly distributed east of the 100th meridian between 2004 and 2006. Between May and September, 1000 m 2 were drag sampled three to six times per site. We developed a zero‐inflated negative binomial model to predict the density of host‐seeking I. scapularis nymphs based on altitude, interpolated weather station and remotely sensed data. Results Variables that had the strongest relationship with nymphal density were altitude, monthly mean vapour pressure deficit and spatial autocorrelation. Forest fragmentation and soil texture were not predictive. The best‐fit model identified two main foci – the north‐east and upper Midwest – and predicted the presence and absence of I. scapularis nymphs with 82% accuracy, with 89% sensitivity and 82% specificity. Areas of concordance and discordance with previous studies were discussed. Areas with high predicted but low observed densities of host‐seeking nymphs were identified as potential expansion fronts. Main conclusions This model is unique in its extensive and unbiased field sampling effort, allowing for an accurate delineation of the density of host‐seeking I. scapularis nymphs, an important component of human risk of infection for B. burgdorferi and other I. scapularis ‐borne pathogens.

Avian host community structure and prevalence of West Nile virus in Chicago, Illinois - Scott R. Loss; Gabriel L. Hamer; Edward D. Walker; Marilyn O. Ruiz; Tony L. Goldberg; Uriel D. Kitron; Jeffrey D. Brawn (Oecologia, 2009)